MENINGKATKAN KEMAMPUAN MENGENAL KONSEP ANGKA MELALUI METODE MULTISENSORI BAGI ANAK AUTIS - Rani Marienzi (Universitas Negeri Padang, 2012)
This study begins of encountered a child with autism who do not understand with the concept of numbers. From the observation children with autism do not know the form of the numbers 1 to 10. This study aims to improve recognize the concept of numbers in children with autism. The design of this study A-B in a single subject research (SSR). As the subject is one child with autism. one child with autism. Assessment in this study consistent in measuring number of correct answers of the figures cited, shown, be taken, and written children with autism were presented as a percentage.